The Impact of Digital Marketing Strategies on Customer Booking Behavior in Mestil Hotel - Suzan Rizpah Akello (Uganda Christian University, 2026)
This report focused on investigating how customer booking behaviour is impacted by digital marketing techniques at Mestil Hotel, Kampala. The reason why most customers prefer the traditional booking option of walk-ins, telephone calls, and third-party booking agents, despite the massive investment made by the hospitality industry of Uganda in digital marketing tools, motivated us to explore the reason and how the hotels in Uganda could improve their digital marketing tools. The research used a mixed-methods research design and employed both the structured questionnaires which were dispatched to the customers and employees as well as a semi-structured interview schedule to obtain data from the supervisory employees among whom was the marketing manager. The literature was a synthesis of the existing theoretical and empirical studies on consumer behaviour and digital marketing in the hospitality industry. The results showed that Mestil Hotel has an extensive digital marketing platform, implying a high-quality site with the ability to make a booking facilitated by active use of social media. Nonetheless, the effect on the behaviour with regards to the booking is partial; the digital channels are effective in the establishment of awareness but minimal in facilitating conversion. The issues that were encountered were channel fragmentation, limitation in data capture, pressure of competition by online travel agencies and customer preferences. The research found that investing in digital marketing is not enough to be able to change established booking behaviours in the absence of strong value propositions, smooth user experiences, and comprehensive marketing campaigns. Some of the recommendations were to maximize direct booking incentives, improve user experience on the site, close the digital divide by educating customers and using customer relationship management to build customer loyalty. This study provides empirical findings of the Ugandan setting to the digital marketing processes in emerging hospitality markets.
Undergraduate